Tackling insecurity in Nigerian schools through multi-media internet solutions (2016)
The problem of insecurity in Nigerian schools was the main crux of this paper. The concept, types and experiences of insecurity was discussed. Four (4) questions were answered using secondary research sources of data. The paper explored the electronic method of security provision and attempted to provide solutions to age-long identified problems of funding, sustainability and diversification of the economy also expatiating on challenges to the adoption of multimedia networks in Nigerian schools. Recommendations included that education insurance policy be inaugurated by the Federal Government of Nigeria (FGN).